Cytokines, Hormones and Cellular Regulatory Mechanisms Favoring Successful Reproduction - Piccinni, Marie-Pierre; Raghupathy, Raj; Saito, Shigeru; Szekeres-Bartho, Julia (Frontiers in Immunology, 2021)
Its semi-allogeneic nature renders the conceptus vulnerable to attack by the maternal immune system. Several protective mechanisms operate during gestation to correct the harmful effects of anti-fetal immunity and to support a healthy pregnancy outcome. Pregnancy is characterized by gross alterations in endocrine functions. Progesterone is indispensable for pregnancy and humans, and it affects immune functions both directly and via mediators. The progesterone-induced mediator - PIBF - acts in favor of Th2-type immunity, by increasing Th2 type cytokines production. Except for implantation and parturition, pregnancy is characterized by a Th2-dominant cytokine pattern. Progesterone and the orally-administered progestogen dydrogesterone upregulate the production of Th2-type cytokines and suppress the production of Th1 and Th17 cytokine production in vitro. This is particularly relevant to the fact that the Th1-type cytokines TNF-α and IFN-γ and the Th17 cytokine IL-17 have embryotoxic and anti-trophoblast activities. These cytokine-modulating effects and the PIBF-inducing capabilities of dydrogesterone may contribute to the demonstrated beneficial effects of dydrogesterone in recurrent spontaneous miscarriage and threatened miscarriage. IL-17 and IL-22 produced by T helper cells are involved in allograft rejection, and therefore could account for the rejection of paternal HLA-C-expressing trophoblast. Th17 cells (producing IL-17 and IL-22) and Th22 cells (producing IL-22) exhibit plasticity and could produce IL-22 and IL-17 in association with Th2-type cytokines or with Th1-type cytokines. IL-17 and IL-22 producing Th cells are not harmful for the conceptus, if they also produce IL-4. Another important protective mechanism is connected with the expansion and action of regulatory T cells, which play a major role in the induction of tolerance both in pregnant women and in tumour-bearing patients. Clonally-expanded Treg cells increase at the feto-maternal interface and in tumour-infiltrating regions. While in cancer patients, clonally-expanded Treg cells are present in peripheral blood, they are scarce in pregnancy blood, suggesting that fetal antigen-specific tolerance is restricted to the foeto-maternal interface. The significance of Treg cells in maintaining a normal materno-foetal interaction is underlined by the fact that miscarriage is characterized by a decreased number of total effector Treg cells, and the number of clonally-expanded effector Treg cells is markedly reduced in preeclampsia. In this review we present an overview of the above mechanisms, attempt to show how they are connected, how they operate during normal gestation and how their failure might lead to pregnancy pathologies.